Analysis of Relationship Between E-Service Quality, E-Recovery Service Quality, and E-Satisfaction Toward Online Purchase Intantion With E-Loyalty as the Mediation Variable - Rachmi Indrianti; Verinita (Enrichment : Journal of Management, 2022)
The purpose of this research is to examine tha relationship between e-service quality, e-recovery service quality, e-satisfaction toward online repurchase intention and e-loyalty as a mediating variable (Study on Shopee Users in the New Normal Era in West Sumatra). The sampling in this study is 234 respondent using purposive sampling technique. The result showed that e-service quality and e satisfaction had a significant effect on e-loyalty, e-recovery service quality had no significant effect on e-loyalty, e-loyalty has a significant effect on online repurchase intention, e-service service quality has no significant effect on online repurchase intention. E-recovery service quality has no significant effect toward online repurchase intention, e-satisfaction has a significant effect toward online repurchase intention, e-service quality had a direct effect toward online repurchase intention and mediated by e-loyalty. E-recovery service quality has no direct effect on online repurchase intention through e-loyalty as a mediating variable. E-satisfaction has a direct effect on online repurchase intention through e-loyalty as a mediating variable.